An intelligent serious game for a multi-device cultural heritage experience. (2017) - Longo, Francesco; Nicoletti, Letizia; Padovano, Antonio; Vetrano, Marco
To date, digital technologies applied to cultural heritage have been mainly devoted to the reconstruction of the original appearance of artefacts and of the museum itself, thus implementing the mere concept of 'virtual museum'. Apart from some isolated cases, museums, and cultural institutions in general, are not so inclined to open out to virtual reality (VR) technologies because they offer the user a detached look at the art collection without actually delivering any cultural and educational content. This research work aims at presenting an innovative multi-device application based on the concept of intelligent serious games (ISGs). The combination of the educational potential of serious games (SGs) with intelligent agents (IAs), which will drive the evolution of the played scenario in accordance to the initial user's profiling and to the sequence of events generated during the museum tour, will create new patterns and promote new strategies for cultural contents dissemination and fruition.